Penyuluhan Strategi Pengentasan Kemiskinan Berbasis Masyarakat di Desa Simpar Kabupaten Batang - Hendy Setiawan; Choirunnisa Choirunnisa (Universitas Negeri Gorontalo, 2023)
Poverty is a problem that continues to hit an area that is always sustainable. It seems that the various policies and programs that have been launched by the Central Government have not been sufficiently optimal and have no significance in creating the welfare of its citizens. Therefore, under these conditions, poverty becomes a very complex problem. It is on the basis of this complexity that the government cannot complete the work itself, so cooperation and collaboration between various parties becomes important. Simpar Village, Bandar Subdistrict, Batang Regency is one of the villages based on data from the Batang Regency Government Planning, Research and Development Agency as a village with poor status. Therefore, seeing this situation, the researchers carried out community service by counseling about poverty alleviation strategies with the modality of community strength itself. Through this counseling, the people of Simpar Village will be increasingly aware of how strong the power of local communities can reduce poverty levels in an area. This service method uses a participatory counseling approach that invites related village officials, community leaders, Village Community Institutions, and also members of the village community. The technique is through opening, filling in the material, forming a Forum Group Discussion, and asking questions in accordance with the presentation of the material. The results showed that the people of Simpar Village had a participative attitude in counseling activities, where discussions and questions and answers went well. It is hoped that with this counseling all components of the Simpar Village community will understand and apply how to overcome poverty they face with the strength of the community itself based on this understanding.